Genetic polymorphism of Î²-casein (CSN2) in zebu and HF crossbreds - Jawane, VB; Ali, S Sajid; Kuralkar, SV; Bankar, PS (Indian Journal of Dairy Science, 2018)
The present research work was carried out to explore the genetic polymorphism of Î²-casein (CSN2) in Zebu (Dangi), HF 62.5% and HF 75% crossbreds maintained at Dangi Cow Research Station, Igatpuri and HF crossbreds maintained at Cattle Breeding Farm, Kopargoan as well as from fields of Ahmednagar of Maharashtra. To determine the beta-casein genotype PCR-RFLP was carried out by using CASB67R and CASB122L primers to amplify the part of exon VII of bovine beta-casein gene. Digestion of PCR amplicons of 251 bp with TaqI restriction enzyme yielded three genotypes A1A1 (213 and 38 bp), A1A2 (251, 213 and 38 bp) and A2A2 (251 bp). Only homozygous genotype A2A2 was observed in all Zebu cattle. Hence gene frequency of A1 allele was zero indicating the fixation of the preferred allele (A2) in naturally evolved native cattle breed. Three genotypes were observed in crossbreds A1A1 (0.03), A1A2 (0.09) and A2A2 (0.88) with the gene frequencies of A1 (0.08) and A2 (0.92). In HF 75% crossbreds gene frequencies were 0.13 (A1) and 0.86 (A2) and genotypic frequencies were 0.06 (A1A1), 0.13 (A1A2) and 0.81 (A2A2) whereas the corresponding gene frequencies in HF 62.5% were 0.03 (A1) and 0.97 (A2) and genotypic frequencies were 0.00 (A1A1), 0.06 (A1A2) and 0.94 (A2A2). Results revealed that gene frequency of A1 allele was higher in the HF crossbreds having 75% exotic germplasm inheritance.